Kleveta jako prostředek sociální kontroly - Kateřina Soukalová (AntropoWebzin, 2015)
The paper presents gossip as a meansof social control. It shows that gossip as informalsocial control is used mainly to maintain a group’snorms and values. It highlights the importanceof the preventive character of gossip, because thepossible existence of gossip affects an individual’sperception of their reputation. The mere fact thatan individual can be an object of gossip or public opinion and thereby be identified as a violator ofstandards, values or norms, has a great influenceon their future social participation and reputationin that group. Within the context of social control,the manuscript presents several theories regardinggossip – the theory of the evolutionary originof gossip, the theory of gossip as a factor whichreinforces social values and norms, the theory ofgossip as a means for purely selfish personal gain,and finally the theory of pro-social gossip and gossipas a form of punishment. It also describes thefundamental functions of gossip and the reasonsfor its spread, and thereby highlights its societalimportance.